2006
DOI: 10.1271/bbb.60038
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effect of Gromwell (Lithospermum erythrorhizon) Extract and Borage Oil on Reversing Epidermal Hyperproliferation in Guinea Pigs

Abstract: To compare the systemic efficacy of borage oil (Borago officinalis: BO) and gromwell (Lithospermum erythrorhizon), two plant species of the Boraginaceae family, epidermal hyperproliferation was induced in guinea pigs by a hydrogenated coconut oil diet for 8 weeks. Subsequently, guinea pigs were fed diets of BO (group HBO), organic extract (group HGO), or water extract (group HGW) of gromwell for 2 weeks. In groups HGO and HGW, proliferation scores and the level of ceramides, the major lipid maintaining epiderm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…3 and 4 A: plasma GLA 0.3 , C: plasma DGLA 1.2 , E: plasma AA 6.2 ; the stratifi ed groups Daily GLA intake was 0.06mg in the control group and 200mg in the GLA group. 1 Values are means SD.…”
Section: Transepidermal Water Loss Stratifi Ed Datamentioning
confidence: 99%
See 1 more Smart Citation
“…3 and 4 A: plasma GLA 0.3 , C: plasma DGLA 1.2 , E: plasma AA 6.2 ; the stratifi ed groups Daily GLA intake was 0.06mg in the control group and 200mg in the GLA group. 1 Values are means SD.…”
Section: Transepidermal Water Loss Stratifi Ed Datamentioning
confidence: 99%
“…The epidermal barrier is composed of intercellular lipid lamellae with ceramides, cholesterol and fatty acids in the stratum corneum. Any barrier disruption increases transepidermal water loss TEWL and epidermal hyperproliferation, both of which are observed in abnormal skin conditions such as essential fatty acid defi ciency 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…As for bioactive components, naphthaquinones such as shikonin and its derivatives have been characterized mostly in organic extracts of gromwell 12,46,47 which have antiproliferative activities in various cancer cells with several mechanisms of action, such as inhibition of DNA topoisomerase, induction of apoptosis by caspase-3 activation, and anti-proliferative activity with down-regulation of activated extracellular signal-regulated kinase (ERK) and activation of phosphorylated Jun N-terminal kinase (JNK) [48][49][50][51] . In previous study, both the organic extract and the water extract of gromwell showed anti-proliferative activity, which suggests that well-characterized bioactive components such as napthaquinones or fatty acids might be extracted with water as well as with organic solvents 10 . In this study, to examine the localization and distribution of substances within the SC, skin surface tape stripping with adhesive tape is a widely accepted and used method.…”
Section: Discussionmentioning
confidence: 89%
“…Depletion of ceramides has been suggested to be an etiological factor for epidermal barrier disruption, the decrease of SC hydration, increased TEWL and epidermal hyperproliferation 10 . We focused on reduced water content rather than TEWL for evaluating the effect of gromwell extract on SC ceramide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation